In vitro and In silico investigation deciphering novel antifungal activity of endophyte Bacillus velezensis CBMB205 against Fusarium oxysporum - Vibha R; Daniela Loaiza Granada; Sinosh Skariyachan; Ujwal P; Sandesh k (Scientific Reports)
Abstract Endophytes from medicinal plants are potential biocontrol agents against Fusarium oxysporum f. sp. cubense (Foc), which is the causative fungus of banana wilt disease. In the present study, the endophytic bacterium was isolated from Globba racemosa and their antagonistic activities against Foc were studied, and the probable molecular mechanism of antagonism was predicted by molecular docking studies. The 16SrRNA sequencing confirmed the endophytic isolate to be Bacillus velezensis CBMB205 (EG2). The antagonistic activities of the isolates by distortion of fungal hyphae were illustrated in SEM. The probable metabolites present in endophytic isolate were identified by FTIR, suggesting the presence of C-H, CH3 and O-H groups. Two major metabolites such as β-amyrin and dihydroxy octadecenoic acid (DA) were confirmed by LC-MS analysis. Molecular docking studies suggested that these metabolites showed potential binding with chitin synthase 1 and fungal 1,3-glucan synthase of pathogenic fungi. The binding energy (BE) of the molecular interaction between β-amyrin and chitin synthase-1 (CS-1), and 1,3-glucan synthase (1,3-GS) were estimated to be -10.17 kcal/mol and − 9.5 kcal/mol, respectively. The BE of the interaction between β-amyrin and CS-1 and 1,3-GS were determined to be -2.43 kcal/mol and 3.4 kcal/mol, respectively. The current study demonstrated the antagonistic activities of EG2 towards Foc and provided a probable molecular mechanism by in silico studies. The study also provides a potential insight into developing endophytic metabolite-based antifungal agents for various agricultural applications.